Study of the Knowledge of Elementary School Health Teachers of Tehran City on How to Control Students' Teeth Injuries at School in - M Vatanpour; CH Azimi; Z Masoumi (Islamic Azad University, 2017)
Background and Aim: Dental injuries are one of the common problems in children. Considering that nowadays, more attention is being paid to dental health and that school health teachers play a key role in the management of dental injuries, this research was designed with the aim of determining the extent of the knowledge of elementary school health teachers of Tehran city on how to control students' teeth injuries at school. Materials and Methods: This research is a cross-sectional study. The questionnaires were given to 280 elementary school health teachers in Tehran city. Of the 280 questionnaires, 216 were answered (77.14%). Data were collected and statistical analysis was performed using descriptive statistics methods and inferential statistics test in two study populations, chi-square independence and Spearman correlation coefficient with 95% confidence interval (CI). Results: Receiving medical emergency training courses affected the responses to the questions regarding the maximum time to restore the teeth to their location (p = 0.001), and the most appropriate action in case of altered consciousness (p = 0.05). Receiving dental emergency training courses had no impact on the responses to any of the other questions (p = 0.231). According to Spearman correlation test results, there was a weak reverse significant correlation between age and the question regarding the most appropriate way to reposition the teeth in this case (p = 0.031 and correlation coefficient = - 0.157), and between work experience and the question regarding distinguishing the tooth type (p = 0.042 and correlation coefficient = - 0. 153). Conclusion: the results indicated that the knowledge of these teachers is not adequate, and that there is a need for education regarding the management of dental injuries. Furthermore, there is no significant correlation between the responses to the questionnaire and receiving dental emergency training courses.